Evolution of the Process for the Preparation of a Selective ErbB VEGF Receptor Inhibitor - Mudryk, Boguslaw; Joshi, Amit; Ortiz, Adrian; Young, Ian S.; Sawyer, James R.; Zheng, Bin; Sugiyama, Masano; Shi, Zhongping; Müslehiddinoğlu, Jale; Corbett, R. Michael; Kronenthal, David R.; Conlon, David A. (Synlett, 2013)
An efficient synthetic route to the potent and selective ErbB VEGF receptor inhibitor, BMS-690514 (1) is described. Strategic modifications in both approach and procedure addressed several issues, which led to a safe, efficient, and economical process for the preparation of multi-kilogram quantities of 1. The convergent route involves alkylation of a suitably protected (3R,4R)-4-aminopiperidin-3-ol with the triethyl(alkyl)ammonium salt of a functionalized pyrrolotriazine 3a followed by deprotection to provide 1 as the crystalline free base.
Keywords: antitumor agents; protected piperidines; protecting groups; heterocycles; Schiff bases